Clinical Psychopharmacology for Neurologists A Practical Guide (Springer International Publishing, 2018)
This book provides neurologists with a basic knowledge of psychiatric medications. It begins with general principles of psychopharmacology and the frequency of psychiatric illness in neurology patients. It goes on to cover psychoactive drugs in the elderly and treating behavioral symptoms of dementia. There is a special emphasis on drug-drug and drug-diet interactions that may be seen in clinical practice. Neurologists, residents, neuropsychiatrists, neuropsychologists and psychiatrists in training will find this practical guide invaluable in numerous clinical settings. .